Isolation of Secondary Metabolites from the Antioxidant Active Fraction of Syzygium aqueum Leaves and Its Docking Simulation on EGFR - Farid Algani; Afrizal Itam; Mai Efdi; Kuntum Suci Mawarni (Biology, Medicine, & Natural Product Chemistry, 2026)
This study aims to isolate secondary metabolites from Syzygium aqueum leaves and assess their suitability for targeting Epidermal Growth Factor Receptor (EGFR) proteins in lung cancer treatment. The methods utilized include maceration, fractionation, chromatography, and molecular docking. The isolated compounds were characterized using UV-VIS spectroscopy, FTIR, and NMR techniques. The compounds were 2',4'-dihydroxy-6'-methoxy-3',5'-dimethylchalcone (DMC) and lupeol. Molecular docking simulations were performed between DMC compounds and EGFR proteins (PDB ID: 1M17, 5D41, 5UG8, 5UG9, and 6LUD). Mutations in the EGFR kinase domain, particularly T790M, L858R, and V948R, confer resistance to first-generation inhibitors, including osimertinib. According to the in-silico docking results, DMC shows promise as an alternative inhibitor candidate. It can maintain interactions with the key residue Lys745 and provides stabilization through Asp855 ansamod Glu762. In contrast, osimertinib relies more on hydrophobic interactions and loses direct contact with Lys745, contributing to decreased affinity. This suggests that DMC may effectively overcome resistance associated with mutations, especially T790M, while maintaining crucial interactions within the ATP binding pocket. Therefore, DMC can be developed into a new non-covalent scaffold for treating lung cancer with EGFR mutations.